A Rapid and Efficient Building Block Approach for Click Cyclization of Peptoids - Samarasimhareddy, Mamidi; Shamir, Mai; Shalev, Deborah E.; Hurevich, Mattan; Friedler, Assaf (Frontiers in Chemistry, 2020)
Cyclic peptide-peptoid hybrids possess improved stability and selectivity over linear peptides and are thus better drug candidates. However, their synthesis is far from trivial and is usually difficult to automate. Here we describe a new rapid and efficient approach for the synthesis of click-based cyclic peptide-peptoid hybrids. Our methodology is based on a combination between easily synthesized building blocks, automated microwave assisted solid phase synthesis and bioorthogonal click cyclization. We proved the concept of this method using the INS peptide, which we have previously shown to activate the HIV-1 integrase enzyme. This strategy enabled the rapid synthesis and biophysical evaluation of a library of cyclic peptide-peptoid hybrids derived from HIV-1 integrase in high yield and purity. The new cyclic hybrids showed improved biological activity and were significantly more stable than the original linear INS peptide.